Myelodysplastic syndromes are propagated by rare and distinct human cancer stem cells in vivo - Woll, P; Kjällquist, U; Chowdhury, O; Doolittle, H; Wedge, D; Thongjuea, S; Erlandsson, R; Ngara, M; Anderson, K; Deng, Q; Mead, A; Stenson, L; et al. (Cell Press, 2014)
Evidence for distinct human cancer stem cells (CSCs) remains contentious and the degree to which differentcancer cells contribute to propagating malignancies in patients remains unexplored. In low- to intermediate-risk myelodysplastic syndromes (MDS), we establish the existence of rare multipotent MDS stem cells (MDS-SCs), and their hierarchical relationship to lineage-restricted MDS progenitors. All identified somatically acquired genetic lesions were backtracked to distinct MDS-SCs, establishing their distinct MDS-propagating function invivo. In isolated del(5q)-MDS, acquisition of del(5q) preceded diverse recurrent driver mutations. Sequential analysis in del(5q)-MDS revealed genetic evolution in MDS-SCs and MDS-progenitors prior to leukemic transformation. These findings provide definitive evidence for rare human MDS-SCs invivo, with extensive implications for the targeting of the cells required and sufficient for MDS-propagation. © 2014 Elsevier Inc.